The Effectiveness of Azolla microphylla Flour Supplementation in Rations on Body Weight, Total Blood Plasma Protein and Total Microbial Contamination of Broiler Carcasses - Ratna Ermawati; Muhammad Mirandy Pratama Sirat; Madi Hartono; Farida Fathul; Fitria Tsani Farda (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2023)
The purpose of this study was to determine the effectiveness of Azolla microphylla flour supplementation in broiler feed rations on body weight, total blood plasma protein and total broiler carcass microbial contamination. The study was conducted for 6 months (May-October 2022) in the broiler cage unit at the Integrated Field Laboratory, Faculty of Agriculture, University of Lampung. This experimental study used four treatments and five replications. Each replicate consisted of five Cobb CP 707broiler strains, bringing a total of 100 broilers. Giving Azolla microphylla flour as a supplement is added to the feed ration with different doses according to broiler body weight, namely P0: ration without Azolla microphylla flour supplementation (control); P1: ration supplemented with 2.5% Azolla microphylla flour; P2 5%; P3 7.5%. Sampling of carcasses and blood serum of 29-day-old broilers was 1 broiler per replication with a total of 20 samples. Samples were sent to the Lampung Veterinary Center to be analyzed for total meat microbial contamination (total plate count) and total plasma protein in blood serum. Data from the test results are arranged in a simple tabular form to be analyzed descriptively. The conclusion of this study wassupplementation with 5% Azolla microphyllaflour in rations were effective to increase body weight gain, maintain total blood plasma protein within the normal range, and maintain total broiler carcass microbial contamination within safe limits for consumption.